Qualitative Detection of Whiteleg Shrimp Disease Using Real-Time PCR - Yanti, Luh Krisna Weda; Satyantini, Woro Hastuti; Sulmartiwi, Laksmi (Department of Aquaculture, 2026)
Indonesia, as the world's fourth-largest shrimp exporter, has experienced a decline in export volume caused by disease outbreaks. This disease is a challenge because shrimp do not have adaptive immunity and rely heavily on innate immunity to survive against pathogens. Therefore, it is necessary to carry out early detection of diseases to reduce cultivation losses. Detection of disease agents in small quantities that have not caused symptoms of disease can be done using PCR tools. Real- Time PCR is widely used because of its fast, accurate visualization results, highly sensitive levels and techniques, and its analysis is qualitative and quantitative. This study only conducted qualitative detection using real-time PCR to determine the presence or absence of pathogens in whiteleg shrimp without quantifying the level of infection. The study included sample preparation, sample extraction, and sample amplification. The number of samples was 75 with WSSV, EMS, and EHP disease test parameters. The number of EHP test parameters was the most tested parameter with 42 tests, then EMS at 22 tests, and finally WSSV with 11 tests. The disease test parameters identified as positive EHP were 16 (38.10%), negative EHP were 26 (61.90%), negative EMS were 22 (100%), and negative WSSV were 11 (100%). Based on Fisher's Exact Test analysis, EHP disease was detected significantly more than EMS and WSSV (p < 0.05). These three parameters are a challenge for farmers because they can cause economic losses.